Quota Formula Review : Initial Considerations. (Policy Papers; Policy Paper, 2012)
Executive Directors welcomed the opportunity to initiate discussions on the quota formula review, which is to be concluded by January 2013. They recalled that the agreement to conduct a comprehensive review of the formula was an integral part of the quota and governance reform agreed in 2010. Directors stressed the importance of agreeing on a quota formula that better reflects members' relative positions in the global economy for future discussions on the 15th General Review of Quotas.